Field‐Switchable Broadband Polarizer Based on Reconfigurable Nanowire Assemblies. (19th December 2016) - Boehm, Sarah J.; Kang, Lei; Werner, Douglas H.; Keating, Christine D.
Abstract : Reconfigurability is one of the most critical properties of nanophotonic systems and, consequently, methods for enabling a significant degree of functionality are highly sought after. However, dynamically responsive control in top‐down fabricated photonic structures often requires extreme conditions and yields moderate modulation capability. In sharp contrast to top‐down methods, directed self‐assembly of micro‐ and nanoparticles offers a distinct avenue for reconfigurable photonics. In the present work, gold nanowire lattices are formed via electric field directed assembly in order to take advantage of their collective optical properties. The lattices are reconfigured on‐demand between two different functional states, in the form of broadband polarizers. By selectively switching the electric field between two orthogonal electrode pairs, a maximum transmission contrast of ≈50% is observed in the near‐infrared regime. Moreover, the reconfigurable transmission spectra, which are highly dependent on the nanowire size and electric field conditions, are reversible. The demonstrated proof‐of‐concept nanowire lattice polarizer provides potential for electrically reconfigurable photonic devices such as ultra‐compact polarization components, electro‐optic switches, and on‐chip modulators. Abstract : In order to build structures with switchable modality that can enable active functionalities, the ability to control organization and rapidly reconfigure particle assemblies is essential. AC electric field directed assembly of gold nanowires to form reconfigurable 2D lattices is employed and a tunable broadband polarizer in a proof‐of‐concept demonstration is presented.